Design And Development Of GPS Navigation Guideline System For Autonomous Underwater Vehicle - Mahirah, Mohamad (UTeM, 2010)

(untitled)
The goal of this project is to design and develop of Global Positioning System (GPS) navigation guidance system for AUV. The GPS is a satellite based on navigation system that sends and receives radio signals. A GPS receiver acquires these signals and provides with information. Using GPS technology you can determine location, velocity and time, 24 hours a day in any weather condition anywhere in the world for free. The device was designed to interface with any GPS receiver capable of outputting NMEA v3.01 RMC, sentences via FT232R UART and USB connection. This project is using Smart GPS Receiver model EB-85A and GPS Engine Board model EB-230. The GPS Locator Utility version 2.61 and GPSTrace version 2.61 is an application program used to enable EB-85A to do the configuration on the unit. This design could easily be expanded and made portable for use in automobiles or other vehicles. This project was intended to demonstrate some ideas that could be used to create a commercially available GPS for AUV. The scientific community uses GPS for its precision timing capability and position information. This device is used in military, aviation, marine and consumer product applications. At s